Vol 2 No 2 September Tahun 2024 KEBIJAKAN KETAHANAN PANGAN SEKTOR PERTANIAN DALAM KAJIAN EKONOMI SYARI’AH: (Studi Kasus Kabupaten Kendal) - Solekhan, Ahmad (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
This study aims to get assesment public policy, including the determination of KEK (Kawasan Ekonomi Khusus Kendal ), land designation, has consequences and risks. Both short and long term risks. In this case, the government must be alert in using its authority to set policies and carry out supervision so that they run well. Benefit is the main goal of Islamic law, so realizing benefit according to this rule is an important reason for a leader to formulate or even ratify a legal product in a country. There are five important things that are benchmarks for the benefit that must be realized by a leader, namely protecting and maintaining the benefit of religion in a country, protecting and maintaining the benefit of the souls of every citizen, protecting and maintaining the benefit of the human mind from various damages, protecting and safeguarding offspring. from extinction and protect and safeguard human property from damageThis article was prepared using a normative juridical library research approach, Normative Juridical Research. Normative Legal Research (normative juridical) is a legal research method carried out by examining mere library materials. This research activity also collects data from various literature. Where researchers do this by taking notes, reading, studying, examining, or analyzing materials that present policies on both a national and regional scale regarding food security that are implemented in Kendal Regency